Depressive Symptoms and Inductive Reasoning Performance: Findings from the ACTIVE Reasoning Training Intervention. - Parisi, Jeanine M.; Franchetti, Mary Kathryn; Rebok, George W.; Spira, Adam P.; Carlson, Michelle C.; Willis, Sherry L.; Gross, Alden L. (Psychology & Aging, 2014)
Within the context of the Advanced Cognitive Training for Independent and Vital Elderly study (ACTIVE; Ball et al., 2002; Jobe et al., 2001; Willis et al., 2006), we examined the longitudinal association of baseline depressive symptoms on inductive reasoning performance over a 10-year period between the reasoning training and control conditions (N = 1,375). At baseline, 322 participants (23%) reported elevated depressive symptoms, defined by a score ⩾ 9 on the 12-item version of the Center for Epidemiological Studies Depression Scale (CES-D; Mirowsky & Ross, 2003; Radloff, 1977). Differences in baseline depressive status were not associated with immediate posttraining gains or with subsequent annual change in reasoning performance, suggesting that the presence of elevated baseline depressive symptoms does not impact the ability to benefit from reasoning training.